2022
DOI: 10.1021/acs.jpcb.2c02968
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Chemisorption by Ammonium and Phosphonium Ionic Liquids: Quantum Chemistry Calculations

Abstract: Carbon capture and storage is an important technological endeavor aiming to improve the ecology by combating global warming. The present work investigates reaction paths that are responsible for CO2 chemisorption by the ammonium- and phosphonium-based ionic liquids containing an aprotic heterocyclic anion 2-cyanopyrrolide. We exemplify that 2 mol of CO2 per 1 mol of the gas scavenger can be theoretically fixed by such ionic liquids. Both the cation and anion participate in the chemisorption. The corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…We found that the −COOH formation mechanism is still the most favored (Δ H = −19.43 kJ mol –1 ), while the cation-based carboxylation at the α-C of phosphonium (Δ H = −2.01 kJ mol –1 ) is as unfavorable as the anion-based carboxylation formation (Δ H = −1.13 kJ mol –1 ). The main reason for the unfavorable cation reaction is that the proton transfer from phosphonium to the [MN] anion is highly uphill at 79.56 kJ mol –1 (Figure S18B) because it breaks the conjugation of the original carbanion; in contrast, it is more favorable for the [2-CNpyr] anion . Our calculation results are consistent with the spectroscopy results (Figure ), supporting the CO 2 chemisorption via the carboxylic acid formation pathway.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the −COOH formation mechanism is still the most favored (Δ H = −19.43 kJ mol –1 ), while the cation-based carboxylation at the α-C of phosphonium (Δ H = −2.01 kJ mol –1 ) is as unfavorable as the anion-based carboxylation formation (Δ H = −1.13 kJ mol –1 ). The main reason for the unfavorable cation reaction is that the proton transfer from phosphonium to the [MN] anion is highly uphill at 79.56 kJ mol –1 (Figure S18B) because it breaks the conjugation of the original carbanion; in contrast, it is more favorable for the [2-CNpyr] anion . Our calculation results are consistent with the spectroscopy results (Figure ), supporting the CO 2 chemisorption via the carboxylic acid formation pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The main reason for the unfavorable cation reaction is that the proton transfer from phosphonium to the [MN] anion is highly uphill at 79.56 kJ mol −1 (Figure S18B) because it breaks the conjugation of the original carbanion; in contrast, it is more favorable for the [2-CNpyr] anion. 36 Our calculation results are consistent with the spectroscopy results (Figure 2), supporting the CO 2 chemisorption via the carboxylic acid formation pathway.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to simplify the analysis, we will focus only on H CR atoms of imidazolium cations, and H 1A atoms of all N-methylene and P-methylene groups of pyrrolidinium and phosphonium cations. These hydrogen atoms demonstrate the highest RDF peaks in each case (Figure S5) and are known to have enhanced acidity and reactivity. …”
Section: Resultsmentioning
confidence: 99%
“…S5) and are known to have enhanced acidity and reactivity. [49][50][51][52] In the series of imidazolium cations with different side chain lengths, the intensity of the first RDF peak at about 2.50 Å is the greatest for C 8 C 1 im + , while for C 2 C 1 im + and C 4 C 1 im + the probabilities are close (Fig. 7a).…”
Section: Local Structure Analysismentioning
confidence: 94%